2019
DOI: 10.1038/s41416-019-0383-z
|View full text |Cite
|
Sign up to set email alerts
|

Ezrin promotes breast cancer progression by modulating AKT signals

Abstract: BACKGROUND: Ezrin, which is known as a cytoskeleton linker protein, is closely linked with the metastatic progression of cancer and is frequently abnormally expressed in aggressive cancer types. However, the possible involvement of Ezrin in metastasis and angiogenesis in breast cancer remains unclear. METHODS: Immunohistochemical analysis of Ezrin was performed on both BC samples (n = 117) and normal epithelium samples (n = 47). In vivo and in vitro assays were performed to validate the effect of Ezrin on AKT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 41 publications
1
45
0
Order By: Relevance
“…Previous studies reported that Ezrin promotes migration, invasion and cancer progression in vitro and in vivo , by interacting with AKT thereby regulating the AKT pathway in breast cancer [ 14 ]. Thus, we investigated whether the ability of Ori and Iru to bind Ezrin in A375 and MKN28, may affect AKT signalling pathways.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies reported that Ezrin promotes migration, invasion and cancer progression in vitro and in vivo , by interacting with AKT thereby regulating the AKT pathway in breast cancer [ 14 ]. Thus, we investigated whether the ability of Ori and Iru to bind Ezrin in A375 and MKN28, may affect AKT signalling pathways.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, since Ezrin has been shown to modulate Matrix Metalloproteinases activity in cancer cells [ 9 , 14 , 24 ], we examined the effect of the two diterpenes on either MMP-9 or MMP-2 activity. To that aim we carried out gel zymography assay on cell-conditioned media from A375 and MKN28 cells, revealing ( Figure 6 A) in both cell lines that treatment with 10 μM of each compound was able to significantly reduce MMP-9 and MMP-2 gelatinolytic activity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cancer-related functions of PCBP2, TIA-1, HuR/ELAVL1, SERBP1, YTHDC2, YTHDF2 (Mapofthecell database) were described above. All experimentally defined partners of eEF1Bγ picked up by Cytoscape to build molecular networks, are linked to cancer as well [2,[125][126][127][128][129][130][131][132].…”
Section: Resultsmentioning
confidence: 99%